Physicochemistry, Nutritional, And Therapeutic Potential Of Ficus Carica – A Promising Nutraceutical - Muhammad Fattah Fazel; Izuddin Fahmy Abu; Mohamad Haiqal Nizar Mohamad; Noor Arniwati Mat Daud; Ahmad Najib Hasan; Zainie Aboo Bakkar; Muhammad Alif Naim Md Khir; Norsham Juliana Nordin; Srijit Das; Muhamad Razin Mohd Razali; Nurul Hana Zainal Baharin; Arashidatul Akmar Ismail (Taylor & Francis, 2025)
Indexed by Scopus/ERA